2004
DOI: 10.1159/000080853
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Dermatomycoses of the Foot as Risk Factors for Acute Bacterial Cellulitis of the Leg: A Case-Control Study

Abstract: <i>Objective:</i> To assess the role of foot dermatomycosis (tinea pedis and onychomycosis) and other candidate risk factors in the development of acute bacterial cellulitis of the leg. <i>Methods:</i> A case-control study, including 243 patients (cases) with acute bacterial cellulitis of the leg and 467 controls, 2 per case, individually matched for gender, age (±5 years), hospital and admission date (±2 months). <i>Results:</i> Overall, mycology-proven foot dermatomycosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
145
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 17 publications
6
145
1
9
Order By: Relevance
“…[14][15][16][17] These studies showed that disruption of the cutaneous barrier (leg ulcer, wound, fissurated toe-web intertrigo, pressure ulcer, or leg dermatosis), venous insufficiency, leg edema, being overweight, fungal infections, history of cellulitis, chronic venous insufficiency, prior saphenectomy, white race, and the presence of Staphylococcus aureus and/or B-hemolytic streptococci in the toe webs to be independently associated with cellulitis.…”
mentioning
confidence: 99%
“…[14][15][16][17] These studies showed that disruption of the cutaneous barrier (leg ulcer, wound, fissurated toe-web intertrigo, pressure ulcer, or leg dermatosis), venous insufficiency, leg edema, being overweight, fungal infections, history of cellulitis, chronic venous insufficiency, prior saphenectomy, white race, and the presence of Staphylococcus aureus and/or B-hemolytic streptococci in the toe webs to be independently associated with cellulitis.…”
mentioning
confidence: 99%
“…It can occur in any part of body but is most common in the lower extremities followed by face, hands, torso, neck and buttocks respectively. 1,2 Various risk factors for cellulitis include traumatic injury, leg ulcers, intertrigo, overweight, lymphedema, diabetes mellitus, vasculitis, previous surgery, radiotherapy and immunocompromised states. 2,3 Causative organisms for cellulitis include Streptococcus pyogenes and Staphylococcus aureus followed by β hemolytic streptococci and gram negative bacilli.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Various risk factors for cellulitis include traumatic injury, leg ulcers, intertrigo, overweight, lymphedema, diabetes mellitus, vasculitis, previous surgery, radiotherapy and immunocompromised states. 2,3 Causative organisms for cellulitis include Streptococcus pyogenes and Staphylococcus aureus followed by β hemolytic streptococci and gram negative bacilli. 4,5 Exact incidence of cellulitis in India is unknown but in USA, it is a common infection affecting 2-3 persons/100 persons/year.…”
Section: Introductionmentioning
confidence: 99%
“…Even though these types of dermatophyte infections do not cause very serious complications, they can adversely affect daily activities, social lives and esthetic appearance and can even require medical intervention (9,10). They may lead to secondary infections and disorders like cellulitis, erysipelas, lymphangitis, asthma, urticaria and atopic dermatitis, which can cause serious problems as they progress (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%